Collie Urea Project Shotts Industrial Park, Shire of Collie & Port of Bunbury : Perdaman Chemicals and Fertilisers Pty Ltd : report and recommendations of the Environmental Protection Authority. - Western Australia. Environmental Protection Authority (Perth, W.A. : Environmental Protection Authority, 2010)
"This report provides the Environmental Protection Authority's (EPA's) advice and recommendations to the Minister for Environment on the proposal to establish a urea production plant in the proposed Shotts Industrial Park, 7.5 kilometres (km) east of Collie, by Perdaman Chemicals and Fertilisers Pty Ltd. The plant would process coal mined from the Griffin coal mine north of the Shotts Industiral Park into urea which would be transported by rail to Bunbury Port for export ..."--P. i.
Cover title.
Includes bibliographical references.
Available on the Environmental Protection Authority website as at 2-Jul-10 at
System requirements: Internet connectivity, World Wide Web browser, and Adobe Acrobat reader.
Digital content preserved
Keywords: Perdaman Chemicals and Fertilisers Pty Ltd; Urea industry -- Environmental aspects -- Western Australia -- Collie Region; Urea as fertilizer -- Environmental aspects -- Western Australia -- Collie Region; Harbors -- Western Australia -- Bunbury; Coal mines and mining -- Western Australia -- Collie Region; Collie Region (W.A.) -- Maps; Bunbury Region (W.A.) -- History